Hubungan Kadar Kolesterol Total dan Trigliserida dengan Kejadian Diabetes Mellitus Tipe 2 di Daerah Pesisir Kota Kendari - Andi Noor Kholidha; Tien Tien; Pranita Aritrina; Fifi Nirmala (Halu Oleo University, 2018)
Background: Type 2 Diabetes mellitus is a common health problem which may result chronic complications. Risk factors such as dyslipidemia, obesity, family history, and genetics play important role in the pathogenesis of the disease. Study on total cholesterol and trygliseride have been carried out in several countries which show relations between total cholesterol and trygliseride with type 2 diabetes mellitus. Purpose: This study aims to determine the relationship between total cholesterol and trigliseride with type 2 diabetes mellitus in the coastal areas of Kendari City. Methods: This study used analytical observational method, with case control approach. The independent variables used in this research is cholesterol total and trigliseride meanwhile the dependent variable is the type2 diabetes mellitus. The location of this research is working area of Public Health Centre located in the coastal area of Kendari City. Result: total cholesterol levels show sig. p value 1,369 based on Chi Square Test, which showed there was no difference in total cholesterol levels. Meanwhile, the triglyceride levels also did not show a significant difference between case and control groups. (p = 0.101). Conclusion: There was no correlation between the increase of total cholesterol level and triglyceride levels with the incidence of DM Type 2 in Kendari City.Keyword: Total Cholesterol, Trigliseride, Type 2 Diabetes mellitus, Coastal Area.